MUSEUM SEBAGAI PUSAT KONSERVASI DAN PRESERVASI BUDAYA: STUDI PADA MUSEUM BULELENG DAN KENDALA PENGELOLAANYA: Konservasi Museum - dina serlyta; Prof.Dr. Drs. I Wayan Mudana, M.Si.; I Putu Putra Yana (Universitas Pendidikan Ganesha, 2026)
The objectives of this study are: (1) to identify the efforts made by the museum to maximize its role as a center for cultural conservation and preservation, (2) to describe the conservation and preservation activities carried out by the Buleleng Museum, (3) to describe the challenges faced by the Buleleng Museum, and to propose recommendations for improvement. This study employed a qualitative descriptive research method, with informants selected using purposive and snowball sampling techniques. The author selected the research location at the Buleleng Museum. In this study, the researcher employed observation, interviews, and document analysis to collect concrete data. The findings indicate that the Buleleng Museum has undertaken several initiatives to support its cultural conservation and preservation functions, such as public outreach, collection inventory, and routine maintenance of museum collections. Conservation activities are carried out by protecting the collections from damage and limiting direct visitor interaction with the collections, while preservation is carried out through routine maintenance and periodic cleaning of the collections. However, conservation and preservation efforts have not yet been fully implemented due to various obstacles, particularly limited human resources, insufficient operational funds, a lack of supporting facilities, and the absence of specialists in the field of conservation and preservation. These conditions have prevented the museum from fully fulfilling its role in preserving the culture of Northern Bali.